To be or not to be vaccinated against COVID-19 – The adolescents’ perspective – A mixed-methods study in Sweden - Nilsson, S.; Mattson, J.; Berghammer, M.; Brorsson, A. L.; Forsner, M.; Jenholt Nolbris, M.; Kull, I.; Lindholm Olinder, A.; Ragnarsson, S.; Rullander, A. C.; Rydström, L. L.; Andréia Garcia de Avila, M. [UNESP]; et al. (Elsevier, 2021)
Vaccination of the population seems to be an important strategy in halting the COVID-19 pandemic in both local and global society. The aim of this study was to explore Swedish adolescents’ willingness to be vaccinated against COVID-19 and its association with sociodemographic and other possible factors. A survey was distributed in Sweden between 7 July and 8 November 2020. The main qualitative question concerned adolescents’ thoughts on vaccination against COVID-19 and evaluated whether the adolescents would like to be vaccinated when a COVID-19 vaccine is made available. In total, 702 adolescents aged between 15 and 19 responded to the questionnaire. A convergent parallel mixed-methods design was used. The results showed that nearly one in three adolescents had not decided if they wanted to get a COVID-19 vaccine, i.e. 30.5%: n = 214. Of the participants 54.3% (n = 381) were willing to be vaccinated. Girls had higher levels of anxiety about the vaccine compared to boys. In addition, high levels of anxiety impacted on the participants’ willingness to be vaccinated. One reason for being undecided about the vaccine was that participants felt they did not know enough about it. Practising social distancing increased willingness to be vaccinated, as reflected in the qualitative results which showed participants wanted to be vaccinated to protect others. The results impart important knowledge to healthcare professionals and contribute to their communication with adolescents about vaccine hesitancy.
Keywords: Adolescence; Anxiety; COVID-19; Mixed-methods; Pandemic; Vaccination hesitancy